Careers Gilding Your Golden Years. - Selinger, C.
This paper provides some useful tips on planning for your retirement, focusing primarily on the many non-financial matters that are not easily apparent. As your career progresses, it becomes even more important to focus on your physical health rather than your financial health. It is also critical to prepare for retirement by developing lifetime professional skills that will not only help your engineering career but will also be valuable in your postwork life
Keywords: Career progresses; Lifetime professional skills; Nonfinancial matters; Physical health; Retirement planning